The Dilemna On Reconceptualizing Natural Resources In Campfire Areas In Zimbabwe - Dzvimbo, Munyaradzi A.; Monga, Monica; Magijani, Freddy (Advances in Social Sciences Research Journal, 2018)
Zimbabwe is indisputably one of the foremost, volatile and vulnerable nations tainted with adverse impacts of the land degradation, poor governance of natural resources, unnecessary burning of the veld and poaching. Hence, there is the need to revisit sustainable environmental management policies and conservation initiatives starting from grassroots level. The CAMPFIRE program in Zimbabwe is one of the strategies designed to tackle environmental management. The conceptual connection of people and conservation of natural resources in Zimbabwe seemed to have evolved towards local ownership and local management. Thus limits of community ownership over natural resources have been reached. According to dominant actors on the conservation scene, the indigenous people in Zimbabwe have not been able to effectively conserve their wildlife and biodiversity and thus in their view a more enforcing style of conservation, separated from local people, is needed again. This study explores and analyses the benefits of conservation and sustainable management of natural resources including wildlife on rural livelihoods with particular focus on rural development. The methods used in this study included focus group discussions, key informant interviews and field observations.